Pendidikan Akidah Akhlak Dengan Metode Brain Based Learning - Arizal, Ardi Sahrul; Fatkhia, Alda Rizka; Humairah, Cut Zahiya Listy; Sugianto, Arif; Umar, Muhammad Aziz; Yulia, Isma (BELAJEA: Jurnal Pendidikan Islam, 2019)
This paper discusses the development of human morality and akidah  using brain based learning. The author are aaindentifies the existence of static learning in moral and akidah education.To create more fun and modern moral learning, a brain based learning method was created.In it contains a strategy about moral akidah learning that uses brain based learning methods that are also combined with learners who are active and effective and in line with it, in order to form human beings who have noble character and strong convictions to disperse Allah, then it is more concerned with planting good person.This learning refers to empowering the potential of the brain so that humans can think critically and cooperatively in supporting the life of their faith and character in accordance with the guidelines of the Qur'an and hadith. In moral akidah education where the times have reached the distribution era, the application of brain based learning methods is very appropriate to be used as a response to the destructive era.